A study of the application of reduction gas analysis in determining the relationship between carboxyhaemoglobin and tissue co levels in brain, heart and skeletal muscle after extreme exposure to co poisoning in rats - Le Roux, C.G.J. (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2007.